FAILURE ANALYSIS OF COMPOSITE CURVED BEAM UNDER BENDING LOAD - ZHOU LongChao; KONG TingTing (Jixie qiangdu)
In this paper,the Solid Composite finite element model is used to calculate the inter-laminar tension and shear stress of the composite curved beam under bending load,and then,the failure strength is predicted. The prediction can match the test results by comparison,show that the analysis of the composite inter-laminar failure is precise,and this method can be used in the aircraft design phase.